Level of Knowledge, Attitudes and Behavior towards Antibiotic Resistance and Use in The Community in Kota Bangun Seberang Village - Riska Febriyanti; Nur Masyithah Zamruddin; Adam M. Ramadhan (Proceeding of Mulawarman Pharmaceuticals Conferences, 2023)
Antibiotics are highly used drugs in Indonesia to treat infections. However, low public knowledge about antibiotics leads to their inappropriate use. Inappropriate use of antibiotics will eventually increase health problems in the form of resistance. This study aims to determine the level of knowledge, attitudes and behavior towards resistance and the use of antibiotics in the community in Kota Bangun Seberang. The method used in this research is observational analysis with cross sectional study approach. Data collection was conducted by interviews using questionnaires consisting of questions about resistance and antibiotic use. Sample collection of 80 people using purposive sampling technique. Data were analyzed univariately and bivariately using the Spearman correlation test. The results showed that the majority of respondents' knowledge level was in the good category at 55%, the majority of respondents' attitudes were in the moderate category at 47.5%, and the majority of respondents' behavior was in the good category at 51.25%. Spearman correlation test showed that there was no correlation between the level of knowledge and attitude, as well as the relationship between attitude and behavior of respondents regarding antibiotic resistance and use (sig > 0.01), and there was a very strong positive correlation between the level of knowledge and antibiotic use behavior of respondents (sig < 0.01).